Impact of an Inpatient Psychiatric Unit on Pediatric Emergency Mental Health Care. Issue 1 (January 2017) - Sheridan, David C.; Johnson, Kyle P.; Fu, Rongwei; Spiro, David M.; Hansen, Matthew L.
Abstract : Objectives: Mental health complaints are a frequent presentation to the pediatric emergency department (PED). It is unclear if having an on-site inpatient pediatric psychiatric unit impacts pediatric mental health care in the acute setting. The objective of this study was to compare PED mental health care between a pediatric tertiary care center with an associated inpatient child psychiatric unit (PAPED) and one that does not (NOPED) with the hypothesis that children have longer lengths of stay (LOS) at the PED without an inpatient unit. Methods: This was a retrospective, observational study of all mental health presentations aged 1 to 18 years to 2 tertiary care PEDs from March 2012 to June 2013 with a final mental health diagnosis International Classification of Diseases, Ninth Revision code. Results: A total of 1409 patient encounters comprised the study group. The PAPED had a significantly higher rate of admission 41.3% versus 18.8% ( P < 0.0001). The LOS was significantly longer at the NOPED compared with the PAPED with a visit of 15.6 versus 6.3, respectively ( P < 0.0001). When LOS was stratified for disposition, patients requiring admission from the NOPED had a significantly longer LOS of 33.4 compared with an emergency department LOS of 8.1 at the PAPED ( P < 0.0001). Conclusions: Mental health care in the PED seems to be affected by having an associated inpatient child psychiatric unit. Further research needs to address this growing problem and ways to utilize community resources to develop safe outpatient plans and divert admission if possible.